Response of microbial structure characteristics and enzyme activity to different altitude - Qiu-liang Cai; Gui-kang Jia; Chun Wei; Ning Zhong; Ling-ling Lv; Jian Li; Hong Pang; Wei Yang (Frontiers in Microbiology)
Studying the influence of altitude on soil microorganisms and enzyme activity is crucial for protecting land environmental changes in karst areas. The study focused on the soil at different altitudes in the Luganyou area, Baise City. The Multidimensional statistical analysis encompassed assessments of soil nutrient properties, soil microorganisms, and soil enzymes across these altitude gradients. The results indicate that enzyme activity in the 0–15 cm soil layer surpasses that in the 15–30 cm soil layer. Catalase, urease, and soil cellulase exhibit consistent trends on both shady and sunny slopes, increasing with altitude. Alpha diversity analysis shows that the abundance and diversity of bacteria and fungi on the shaded side exhibit the following trend of low altitude > high altitude. In contrast, on the sunny side, bacterial richness displayed a decreasing-increasing pattern with rising altitude, while the diversity trend mirrored that of the shady side. Overall, fungal richness on the sunny side exhibited a slight decrease, whereas diversity increased with altitude. Across shady slopes, overall soil nutrient levels tend to increase with altitude. The comprehensive ecological stoichiometry analysis of the soil indicated an elevated C/N ratio, while the N/P and C/P ratios were relatively low on both shady and sunny slopes. These findings suggest that the study area as a whole is constrained by N availability. Correlation and redundancy analyses revealed that organic matter is the primary factor influencing enzyme activity in shaded slopes, while organic matter and available phosphorus are the key factors affecting enzyme activity in sunny slopes. The key nutrient factors affecting microorganisms include total nitrogen content, organic matter content, as well as enzyme factors such as invertase, catalase, and acid phosphatase. In summary, the study revealed a negative correlation between microbial diversity on shady slopes and altitude in the low altitude areas of southwest China (160–380 m). Additionally, bacterial richness on sunny slopes displayed a “low-high-low” trend, underscoring the significance of organic matter (R2 = 0.683) and available phosphorus (p < 0.05) as pivotal drivers of microbial communities. These findings aim to offer a theoretical framework for guiding crop cultivation, land management, and enhancement strategies in southwestern China.